Exploring the impact of Chat-GPT on India and global socioeconomic Landscape: Opportunities, Challenges, and Implications - Mishra, Nirbhay; Gupta, Manish; Harsh, Kumar; Ojha, Divya; Mitra, Ayushman; Gupta, Onkar (International Journal of Computer Sciences and Engineering, 2026)
The advent of Chat-GPT, an advanced conversational AI technology developed by OpenAI, has revolutionized human-computer interactions and holds significant implications for India and the global landscape. This research paper explores the impact of Chat-GPT on various domains, including customer service, education, content generation, and communication, and investigates the potential benefits, challenges, and implications that arise from its widespread adoption. Chat-GPT, powered by the Transformer architecture, has the ability to understand and generate human-like text, making it a powerful tool in natural language processing and machine learning. In customer service, businesses in India can leverage Chat-GPT-powered chatbots to enhance customer experiences, streamline support processes, and increase satisfaction by providing prompt and accurate responses. Similarly, in education, Chat-GPT can offer personalized learning experiences, aiding students with tutoring, homework assistance, and access to educational resources, ultimately enhancing engagement and learning outcomes. The transformative potential of Chat-GPT extends to content generation and curation, where it can automate the creation of written content, saving time and effort for content creators in India. Furthermore, the adoption of AI technologies like Chat-GPT can foster economic growth, drive digital transformation, and create job opportunities in AI-related fields, contributing to India's socio-economic development. However, the integration of Chat-GPT also presents challenges and ethical considerations. Issues such as bias, fairness, privacy, and transparency must be addressed to ensure responsible and beneficial use of the technology. Policymakers, businesses, and researchers play a crucial role in navigating these challenges to maximize the positive impact of Chat-GPT while mitigating potential drawbacks. Through a comprehensive analysis of existing literature, case studies, and expert insights, this research paper provides valuable insights and recommendations for stakeholders. It highlights the transformative potential of Chat-GPT and the need for responsible integration into various spheres of society. By understanding the impact of Chat-GPT on India and the wider world, this research aims to contribute to the advancement of AI technologies and their ethical deployment, ultimately shaping a future where AI serves the collective benefit of society.